2022
DOI: 10.1155/2022/8622022
|View full text |Cite|
|
Sign up to set email alerts
|

Arabic Speech Analysis for Classification and Prediction of Mental Illness due to Depression Using Deep Learning

Abstract: Depression is a global prevalent ailment for possible mental illness or mental disorder globally. Recognizing depressed early signs is critical for evaluating and preventing mental illness. With the progress of machine learning, it is possible to make intelligent systems capable of detecting depressive symptoms using speech analysis. This study presents a hybrid model to identify and predict mental illness from Arabic speech analysis due to depression. The proposed hybrid model comprises convolutional neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This is because the achieved findings can be used to identify key indicators of depression in spoken Arabic, such as speech patterns, intonation, and pauses. These indicators can then be used to identify individuals who may be suffering from depression and help physicians, psychiatrists, and psychologists provide more effective treatment as in [22]. The mental health issues, such as depression and anxiety, are becoming more common, and people are recognizing the need to prioritize their mental health as well as their physical health.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the achieved findings can be used to identify key indicators of depression in spoken Arabic, such as speech patterns, intonation, and pauses. These indicators can then be used to identify individuals who may be suffering from depression and help physicians, psychiatrists, and psychologists provide more effective treatment as in [22]. The mental health issues, such as depression and anxiety, are becoming more common, and people are recognizing the need to prioritize their mental health as well as their physical health.…”
Section: Related Workmentioning
confidence: 99%
“…Reddit's post-dataset cleaning process is related to removing personal information, punctuation marks, and URLs. CNN +SVM [22] Intelligent system to detect depressive symptoms using speech analysis Basic Arabic Vocal Emotions Dataset (BAVED) 90 and 91.60…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%